Post-stroke speech and language disorders. An epidemiological study - Mickiewicz, Julia; Rutkiewicz-Hanczewska, Małgorzata; Kaźmierski, Radosław (Papers in Linguistics, 2022)
The article is devoted to the epidemiology of speech and language disorders that occur in people after a stroke, with particular emphasis on aphasia and dysarthria. The data was obtained on the basis of retrospective analysis of medical records collected in the Department of Neurology and Vascular Diseases of the Nervous System in the Ministry of Interior and Administration Hospital in Poznań, including discharge reports of 234 patients with a stroke who were admitted to the facility in 2017. The results of the analyses were compared with the latest reports on the epidemiology of language disorders published in international literature. This is one of the first studies in this field concerning the Polish population.